The mitochondrial genome of Brachycephalus brunneus (Anura: Brachycephalidae), with comments on the phylogenetic position of Brachycephalidae - Pie, Marcio R.; Stroher, Patricia R.; Bornschein, Marcos R. [UNESP]; Ribeiro, Luiz F.; Faircloth, Brant C.; McCormack, John E. (Elsevier B.V., 2017)
The mitochondrial genome of Brachycephalus brunneus was determined by next generation sequencing of mitochondrial DNA. Without its control region, it has a total length of 15,485 bp, consisting of 37 genes: 13 protein-coding genes, 2 rRNA genes, and 22 tRNA genes. Except for eight tRNAs and the nd6 gene, all other mitochondrial genes are encoded on the heavy strand. ATG and ATC act mainly as the initial codon in 10 protein coding genes, whereas nd2 and cox1 use ATT and nad3 uses ATA. Gene order is generally consistent with that observed in closely-related families. The cloverleaf structures for trnS1 and trnC lacked the DHU-stem and DHU-loop, respectively. Phylogenetic analyses of mitogenomes of closely-related families indicate that Brachycephalidae is more closely related to Craugastoridae than to Eleutherodactylidae. This is the first sequenced mitochondrial genome for the entire Brachycephalidae and can provide the basis for the development of mitochondrial markers for other members of the family, including many species that are critically endangered. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Anuran; Brazil; Terrarana; Atlantic forest